Exploring the role of natural vegetation in shaping bee diversity, functional space, and species turnover across agricultural landscapes - Florencia Vicencio-Olivares; Manuel López-Aliste; Pablo Díaz-Siefer; Ingrid N. Gomes; Christian Jofré-Pérez; Luis Flores-Prado; Juan L. Celis-Diez; Francisco E. Fontúrbel (Global Ecology and Conservation, 2025)
Agricultural expansion contributes to the degradation and fragmentation of natural ecosystems, resulting in the decline of wild pollinators, particularly bees. However, sustainable practices, such as preserving patches of native vegetation around crops, can help enhance pollinator diversity. Based on the ecological intensification framework, we investigated how the conservation of natural vegetation areas near apple and cherry orchards influences the composition, functional space, and turnover of bee species within the studied communities in a Mediterranean-type ecosystem of central Chile. We found a dominance of generalist bees in apple and sweet cherry orchards, and a greater taxonomic richness in crops surrounded by a higher proportion of natural vegetation. However, the functional space and species turnover in the crops during the analyzed years were low, likely due to environmental filters imposed by monoculture practices and the dominance of bee communities consisting mostly of generalist species. These findings highlight the critical role of surrounding natural vegetation areas in supporting bee functional diversity and taxonomic richness. Despite functional diversity and species turnover being low due to monoculture constraints, preserving natural habitats is essential for a more diverse community of bees. This study sheds light on how wild bee communities respond to agricultural landscapes and highlights the role of conserving natural areas in mitigating the impacts of agricultural intensification on pollinators.